A 600 kyr reconstruction of deep Arctic seawater δ 18 O from benthic foraminiferal δ 18 O and ostracode Mg ∕ Ca paleothermometry - J. R. Farmer; K. J. Keller; R. K. Poirier; G. S. Dwyer; M. F. Schaller; H. K. Coxall; M. O'Regan; T. M. Cronin (Climate of the Past, 2023)
The oxygen isotopic composition of benthic foraminiferal tests ( δ 18 O b ) is one of the pre-eminent tools for correlating marine sediments and interpreting past terrestrial ice volume and deep-ocean temperatures. Despite the prevalence of δ 18 O b applications to marine sediment cores over the Quaternary, its use is limited in the Arctic Ocean because of low benthic foraminiferal abundances, challenges with constructing independent sediment core age models, and an apparent muted amplitude of Arctic δ 18 O b variability compared to open-ocean records. Here we evaluate the controls on Arctic δ 18 O b by using ostracode Mg/Ca <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="37pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1e3d1d11bbe5435973a8908703b160da"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-19-555-2023-ie00003.svg" width="37pt" height="14pt" src="cp-19-555-2023-ie00003.png"/></svg:svg> paleothermometry to generate a composite record of the δ 18 O of seawater ( δ 18 O sw ) from 12 sediment cores in the intermediate to deep Arctic Ocean (700–2700 m) that covers the last 600 kyr based on biostratigraphy and orbitally tuned age models. Results show that Arctic δ 18 O b was generally higher than open-ocean δ 18 O b during interglacials but was generally equivalent to global reference records during glacial periods. The reduced glacial–interglacial Arctic δ 18 O b range resulted in part from the opposing effect of temperature, with intermediate to deep Arctic warming during glacials counteracting the whole-ocean δ 18 O sw increase from expanded terrestrial ice sheets. After removing the temperature effect from δ 18 O ...